ECOSYSTEM BASED MANAGEMENT FOR BIODIVERSITY RESTORATION IN GERMANY - Dr Tariq Mahmood; Aftab Aslam; Dr Mahnoor Pervez; Iqra Bibi; Sadia Rafique; Khubaib Shakoor; Faisal Shahzad; Mehvish Parveen; Muhammad Ammad Abu Bakkar; Samia Zain; et al. (International Journal of Contemporary Issues in Social Sciences, 2023)
The Ecosystem-based management approach (EBM) was developed as a result of the Conferences of the Parties (CoP) to the Convention on Biological Diversity (CBD) and was conceived as a complex approach to understanding or as a guideline for the sustainable management of all types of biological resources, supplemented by twelve guiding principles and five operational guidance points developed at a Workshop in Malawi in 1998.The goal of this review paper was to assess the effectiveness of a less commonly employed strategy of eco-system-based approach to manage natural resources particularly forests in Germany. The theoretical framework of EBM in particular, as well as traditional or more common management approaches like Sustainable Forest Management (SFM), Close to Nature Management System, and Multi-Functional Forestry in general, were evaluated. Online published papers, articles, and scientific data were consulted using Google Scholar, Science Direct, and, the Online Library Catalogue in a strong scientific, systematic and filtering procedure, which provided a sound base for assessing and summarizing the results. The findings showed that, despite the inherent biases, scientific, societal, and institutional problems, the EBM method, on the whole was, a beneficial way forward in resolving complicated concerns in forest resource management if implementation/operational issues were addressed. Forest strategy 2020 for German forestry sector envisaged that forest must be viewed as a resource which was simultaneously a part of nature and national economy. The changing role of forests from timber harvesting to climate stewardship, environmental protection, nature conservation, wildlife preservation, biodiversity conservation along with leisure and recreation values resulted in conflicting goals and competing agendas in some places. Addressing these complex interrelationships and diverse needs necessitated a comprehensive and holistic management strategy, none other than EBM outperforms other management systems to fill the void.